Dietary Patterns and Their Associations With the FTO and FGF21 Gene Variants Among Emirati Adults - Naja, Farah; Itani, Leila; Hammoudeh, Sarah; Manzoor, Shaista; Abbas, Nada; Radwan, Hadia; Saber-Ayad, Maha (Frontiers in Nutrition, 2021)
Purpose: To examine the dietary patterns and their associations with the FTO and FGF21 gene variants among Emirati adults. Methods: Using a cross-sectional design, healthy adult male and female Emiratis (n=194) were recruited from primary health care centers in Sharjah, UAE. Participants completed a 61-item semi-quantitative food frequency questionnaire. In addition, a saliva sample was obtained for the genetic analysis. Genotyping was performed for FTO rs9939609(A>T), FTO rs9930506(A>G), FGF21 rs838133 (A > G) and FGF21 rs838145 (A > G). Dietary patterns were derived using the principal component analysis. Logistic regression analyses were used to examine the association of dietary patterns with genetic variants. Results: Three dietary patterns were identified: “Western”: consisting of fast food, sweets, and processed meat; “Traditional Emirati” rich in vegetables, traditional Emirati-mixed-dishes, and whole dairy; while whole grains, low-fat dairy, and bulgur were components of the “Prudent” pattern. Subjects with genotype A/T of the FTO rs9939609 were 2.52 times more likely to adhere to the Western pattern compared to subjects with genotype T/T. Compared with subjects with G/G, those with the A/G genotype of the FTO rs9930506-G were more likely to follow a Western diet (OR: 2.55; 95%CI: 1.03-6.33). Participants with homozygous genotype of the risk allele (A/A) of the gene FGF21 rs838133-A were 3.11 times more likely to adhere to the Traditional pattern as compared to subjects with genotype G/G. Conclusions: The findings of this study are important to develop evidence-based targeted preventive recommendations, especially among individuals with a higher susceptibility to obesity and related diseases.